Cutwaters Before Rams: an experimental investigation into the origins and development of the waterline ram. (1st March 2017) - Murray, William M.; Ferreiro, Larrie D.; Vardalas, John; Royal, Jeffrey G.
Abstract : Students at Stevens Institute of Technology (Hoboken, NJ, USA) investigated the reasons for an elongated projection at the bow of Mediterranean galleys. Using a 1:20 base model adapted from the Trireme Trust's Olympias fitted with: 1) an elongated projection; and 2) a control bow similar to excavated merchant ships, tow‐tank tests were carried out at various speeds. Hydrodynamic resistance and power were calculated for each bow type. Above speeds corresponding to 6 knots, the cutwater bow significantly attenuated the model's bow waves when compared to the control bow. These results were then compared to those of the ship with a ram‐type bow from experiments conducted in 1985 at the National Technical University of Athens, which showed similar wave‐attenuating characteristics. Abstract : 冲撞角出现前的船首破浪材༚水线冲撞角起源与发展的实验性研究 斯蒂文斯理工学院 (美国新泽西州霍博肯市) 的学生探索造成地中海单层甲板大帆船-首存在延伸突出部的原因。实验以"三层桨战船信托"的 Olympias 号为蓝本采用1:20的比例做出模型同时加装-1) 一个延伸突出部-2) 一个同已发掘商船相似的"可调节-首", 并在拖曳水池中以各种速度进行了实验。每种船首形式的水动阻力及水动力都经过计算。在速度超-6节时, 相对于"可控"船首, 船首破浪材使模型船首波浪显著衰减。这些结果进而与1985年雅典国家理工学院为实验而打造的冲撞角式船首-舶的实验结论相比较, 两-都显示了相似的波浪衰减特征。 沖撞角出現前的船首破浪材༚水線沖撞角起源與發展的實驗性研究 斯蒂文斯理工學院 (美國新澤西州霍博肯市) 的學生探索造成地中海單層甲板大帆船-首存在延伸突出部的原因。實驗以"三層槳戰船信托"的 Olympias 號為藍本采用1:20的比例做出模型同時加裝-1) 一個延伸突出部-2) 一個同已發掘商船相似的"可調節船首", 並在拖曳水池中以各種速度進行了實驗。每種船首形式的水動阻力及水動力都經過計算。在速度超-6節時, 相對於"可控"船首, 船首破浪材使模型船首波浪顯-衰減。這些結果進而-1985年雅典國家理工學院為實驗而打造的沖撞角式船首-舶的實驗結論相比較, 兩者-顯示了相似的波浪衰減特征。